Monitoring of carbon isotope composition of snow cover for Tomsk region - Akulov P. A. Petr Anatoljevich; Volkov Yu. V. Yury Viktorovich; Kalashnikova D. A. Darjya Andreevna; Markelova A. N. Anna Nikolaevna; Melkov V. N. Viktor Nikolaevich; Simonova G. V. Galina Vladimirovna; Tartakovsky V. A. Valery Abramovich (2016, 2016)
Title screen